On the Performance of a Simple Adaptive Relaying Protocol for Wireless Relay Networks - Yonghui Li; Vucetic, B. (VTC Spring 2008 - IEEE Vehicular Technology Conference, 2008)
Distributed coding has been shown to be an effective scheme to explore cooperative spatial diversity in wireless relay networks. To date, the distributed coding schemes employ two major relaying protocols, decode and forward (DAF) and amplify and forward (AAF). They suffer from a disadvantage of either noise amplification or error propagation. In this paper, we propose a simple adaptive relaying protocol (ARP) for general relay networks. For the proposed approach, all relays are included into one of two relay groups, referred to as a DAF relay group and an AAF relay group. All relays, which decode correctly, are included in the DAF relay group, and other relays, which could not decode correctly, are included in the AAF relay group. Performance analysis of the proposed adaptive relaying protocol is carried out, and compared with other relaying protocols. It is shown that the proposed adaptive relaying protocol benefits from a significant coding gain contributed from the DAF relay group compared to a pure AAF relay protocol and simultaneously circumvent the detrimental effects of error propagation due to the imperfect decoding at relays in a DAF relay protocol, thus always outperforming both the AAF and DAF relaying protocols in all SNR regions.